Return to Play and Performance in the Women's National Basketball Association After Anterior Cruciate Ligament Reconstruction. Issue 9 (16th September 2020) - Tramer, Joseph S.; Khalil, Lafi S.; Ziedas, Alexander; Mehran, Nima; Okoroha, Kelechi R.
Background: The incidence of anterior cruciate ligament (ACL) injuries in Women's National Basketball Association (WNBA) athletes continues to increase. There is a paucity of data regarding return-to-play (RTP) rates and performance after ACL reconstruction in these athletes. Purpose: To quantify RTP rates and performance after ACL reconstruction in WNBA athletes. Study Design: Cohort study; Level of evidence, 3. Methods: All ACL tears sustained in the WNBA from 1997 through 2018 were identified. Body mass index (BMI), age, and position at the time of injury were collected for each player. RTP rates were calculated, and performance data were collected for each player before and after injury to determine changes in playing time and statistical performance. Players who successfully returned to play after ACL reconstruction were compared with a group of healthy controls who were matched by age, years of experience, position, height, and BMI. Statistics at 1 and 3 years after injury were compared to assess acute and longitudinal changes in performance relative to preinjury baseline. Results: A total of 59 WNBA players sustained ACL tears during the study period, and 41 (69.5%) were able to successfully RTP. Players played a mean of 7.5 ± 12.8 fewer games, played 5.0 ± 9.2 fewer minutes per game, and scored 3.7 ± 5.0 fewer points per game in their first year after RTP compared with the year before injury. Athletes with ACL reconstruction demonstrated significantly decreased performance measures regarding games played, games started, minutes, rebounds, assists, and blocks per game in their first season after RTP compared with control athletes in the same indexed year; however, these differences resolved by year 3 after surgery. Conclusion: WNBA athletes have a high RTP rate after ACL reconstruction. Players may experience an initial decrease in playing time and performance when returning to play; however, these variables were found to return to baseline over time.